Rosuvastatin induced photolocalized purpura. Issue 9 (23rd September 2022) - Thabouti, Marwa; Gahriani Fetoui, Nadia; Manaa, Linda; Rouatbi, Jacem; Sriha, Badreddine; Ben Salem, Chaker; Denguezli, Mohamed
Abstract : Statins are a widely used class of drug, usually safe and well‐tolerated. Their cutaneous side effects are exceedingly rare. We describe a case of photoexposed purpuric eruption mediated by rosuvastatin.